Revisiting the Role of Interleukin-1 Pathway in Osteoarthritis: Interleukin-1α and -1β, and NLRP3 Inflammasome Are Not Involved in the Pathological Features of the Murine Menisectomy Model of Osteoarthritis - Nasi, Sonia; Ea, Hang-Korng; So, Alexander; Busso, Nathalie (Frontiers in Pharmacology, 2017)
Background: Innate immune response components such as toll-like receptors (TLRs) and NLRP3-inflammasome act in concert to increase IL-1α/β secretion by synovial macrophages. Previous results suggest that IL-1α/β could be an important mediator involved in the pathogenesis of osteoarthritis (OA). Objectives: The aim of our study was to evaluate the role of NLRP3, IL-1β and IL-1α in the menisectomy (MNX) model of murine OA. Methods: Murine chondrocytes (CHs) and bone marrow-derived machrophages (BMDM) were stimulated with hydroxyapatite (HA) crystals, a form of calcium-containing crystal found in human OA, and IL-1β and IL-6 secretion assayed by ELISA. Conversely, the ability of IL-1β and IL-6 to induce CHs calcification was assessed in vitro by Alizarin red staining. Knees from 8-10 weeks old C57Bl/6J wild-type (WT) (n=7), NLRP3-/- (n=9), IL-1α-/- (n=5) and IL-1β-/- (n=5) mice were menisectomized, using the sham-operated contralateral knee as control. 8 weeks later, knee cartilage degradation and synovial inflammation were evaluated by histology. In addition, apoptotic chondrocytes, metalloproteases activity and collagen-type 2 expression were evaluated in all mice. Joint calcification and subchondral bone parameters were quantified by CT-scan in WT and IL-1β-/- menisectomized knees. Results: In vitro, HA crystals induced significant increased IL-6 secretion by CHs, while IL-1β remained undetectable. Conversely, both IL-6 and IL-1β were able to increase chondrocytes mineralization. In vivo, operated knees exhibited OA features compared to sham-operated knees as evidenced by increased cartilage degradation and synovial inflammation. In menisectomized KO mice, severity and extent of cartilage lesions were similar (IL-1α-/- mice) or exacerbated (IL-1β-/- and NLRP3-/- mice) compared to that of menisectomized WT mice. Metalloproteases activity, collagen-type 2 expression, chondrocytes apoptosis and synovial inflammation were similar between KO and WT mice menisectomized knees. Moreover, the extent of joint calcification in osteoarthritic knees was comparable between IL-1β-/- and WT mice. Conclusions: MNX knees recapitulated features of OA, i.e, cartilage destruction, synovial inflammation, cell death, and joint calcification. Deficiency of IL-1α did not impact on the severity of these features, whereas deficiency of IL-1β or of NLRP3 led to increased cartilage erosion. Our results suggest that IL-1α and IL-1β are not key mediators in this murine OA model.